Determinants of Effective Tax Rate: Empirical Evidence From Selected Manufacturing Industries in Bangladesh - Sharif, Md. Jamil; Khan, Shawrin Ahmed (Universitas Negeri Semarang, 2023)
Purpose: The objective of this study is to conduct an empirical investigation of financial and operational firm specific factors that have an impact on the effective tax rate (ETR) for Bangladeshi manufacturing firms operating in a variety of industries. Method: The study solely focused on three different production industries: Pharmaceuticals and Chemicals, Engineering, and Ceramics. At least six years’ set of panel data have been collected from each industry between 2016 and 2021 in order to conduct an analysis of the panel corrected standard error model (PCSE). Thus, the PCSE model is used to conduct an analysis on a total of 265 observations derived from 44 different company listed in DSE. Findings: Out of eight financial and operational factors, firm size and profitability has a significant positive correlation with ETR in practically every sector separately and collectively. The findings are supported by political cost theory that suggests large firms have to pay more taxes due to political attention. One exception has been found regarding Ceramics sector where firm size has insignificant negative impact on ETR. This is reinforced by the political power theory, which states that politically influential corporations are less likely to voluntarily pay taxes because of the incentives provided by the power they wield in politics. On the other hand, Interest coverage ratio, Interest to sales ratio, capital intensity, firm age leverage has also significant impact on the effective tax rate in both model ETR1 and ETR2 differently across sectors. This study also concludes that there is variation among industry to industry and little bit of year indicators. Novelty: The study investigates the factors of manufacturing companies empirically and contributes to the variety of taxation issues among various manufacturing sectors. According to the authors’ best knowledge, there has been very little research on taxes, hence this study is a completely new contribution to Bangladesh’s manufacturing sector. Keywords: Effective Tax Rate; Dhaka Stock Exchange; Political Cost Theory; Political Power Theory